2011
DOI: 10.1002/asia.201100020
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical and Electronic Rules in Fullerene‐Based Compounds

Abstract: The discovery of buckminsterfullerene C(60) opened up a new scientific area and stimulated the development of nanoscience and nanotechnology directly. Fullerene science has since emerged to include fullerenes, endohedral fullerenes (mainly metallofullerenes), exofullerenes, and carbon nanotubes as well. Herein, we look back at the development of fullerene science from the perspective of epistemology by highlighting the proposed main rules or criteria for understanding and predicting the structures and stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 89 publications
(130 reference statements)
1
12
0
Order By: Relevance
“…It is important to note that our predicted relative aromaticity order based on the BRE method is in very good agreement with the results of Gan et al [36,37] for the 4/5 and 4/4 type bonds. However, we do not accept the position in the relative aromaticity order predicted by Gan et al for the 6/6 bond nor for those bonds which contain heptagons.…”
Section: Local Aromaticity Of C 24 Isomerssupporting
confidence: 85%
See 1 more Smart Citation
“…It is important to note that our predicted relative aromaticity order based on the BRE method is in very good agreement with the results of Gan et al [36,37] for the 4/5 and 4/4 type bonds. However, we do not accept the position in the relative aromaticity order predicted by Gan et al for the 6/6 bond nor for those bonds which contain heptagons.…”
Section: Local Aromaticity Of C 24 Isomerssupporting
confidence: 85%
“…Gan et al [36,37] performed calculations on carbon polyhedra that consisted of squares, pentagons, hexagons, and heptagons using the density functional theory (DFT) method, and based on their binding energy, the following stability order of subunits within carbon polyhedrons was determined: 6/7 > 4/6 > 5/5 > 4/5 > 4/4 4/7 > 5/7 > 7/7 > 5/6 > 6/6…”
Section: Local Aromaticity Of C 24 Isomersmentioning
confidence: 99%
“…At a temperature above 2,100 K, however, the heptagon-incorporating C 68 becomes the most abundant species as entropic factors have a decisive role in their relative Gibbs free energies and relative concentrations/abundances (Supplementary Tables S8 and S9). In agreement with this prediction about the temperature-dependent stability, several theoretical studies have suggested the prevalence of heptagons in the world of the cage-closed all-carbon allotropes1112131415161718192021232425263536. Experimental corroboration of such a prevalence of heptagons heavily depends on the in situ capture of heptafullerene in the carbon clustering venue for the growth of the whole family of fullerenes.…”
Section: Discussionmentioning
confidence: 63%
“…A bare heptafullerene[62] with C s -symmetry23, as well as the exohedral heptagon-containing C 68 X 4 (X=H, F, Cl)24, has been calculated to be more stable than all the classical non-heptagon isomers. Very recently, a number of smaller heptafullerenes (C 46 –C 58 ) have also been suggested to be viable182526. However, experimental confirmation of the existence of heptagons in the family of fullerenes is still a challenge for chemists and physicists.…”
mentioning
confidence: 99%
“…2 Since the invention of the resistive heating method, 3 a series of monometallofullerenes and dimetallofullerenes were synthesized in bulk quantities. 2 Since the invention of the resistive heating method, 3 a series of monometallofullerenes and dimetallofullerenes were synthesized in bulk quantities.…”
Section: Introductionmentioning
confidence: 99%